1994
DOI: 10.21273/jashs.119.6.1248
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining Polyphenol Oxidase, Peroxidase, and Leaf-blackening Activity in Protea

Abstract: Premature leaf blackening in Protea severely reduces vase life and market value. The current hypothesis suggests that leaf blackening is induced by a sequence of events related to metabolic reactions associated with senescence, beginning with total depletion of leaf carbohydrates. It is thought that this carbohydrate depletion may induce hydrolysis of intercellular membranes to supply respiratory substrate, and subsequently allow vacuole-sequestered phenols to be oxidized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…The metabolism of phenolic compounds involves the activation of oxidative enzymes, such as PPO and POD, which catalyse the oxidation of phenols to quinones (Vaughn and Duke, 1981 [60] ; Thipyapong et al, 1995 [57] ). Numerous researchers have demonstrated the activity of both enzymes to be affected by different types of biotic and abiotic stress (McConchie et al, 1994 [35] ; Cheng and Crisoto, 1995 [15] ; Thipyapong et al, 1995 [57] ; Söderhäll, 1995 [52] ; Kwak et al, 1996 [30] ; Thipyapong and Stellens, 1997 [58] ), notable among the latter being the nutritional status of elements such as B and Ca (Kawai et al, 1995 [25] ; Söderhäll, 1995 [52] ; Kwak et al, 1996 [30] ; Cakmak and Römheld, 1997 [10] ; Tomasbarberan et al, 1997 [59] ; Kim and Heinrich, 1997 [29] ; Ruiz et al, 1998 [46] , 1999 [47] ). In our experiment, the N dosage significantly affected the activities of PPO and POD (p < 0.001; Table 1), N2 and especially N1 presenting the highest activities, while N3 gave the lowest, with a reduction of 42 and 58 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolism of phenolic compounds involves the activation of oxidative enzymes, such as PPO and POD, which catalyse the oxidation of phenols to quinones (Vaughn and Duke, 1981 [60] ; Thipyapong et al, 1995 [57] ). Numerous researchers have demonstrated the activity of both enzymes to be affected by different types of biotic and abiotic stress (McConchie et al, 1994 [35] ; Cheng and Crisoto, 1995 [15] ; Thipyapong et al, 1995 [57] ; Söderhäll, 1995 [52] ; Kwak et al, 1996 [30] ; Thipyapong and Stellens, 1997 [58] ), notable among the latter being the nutritional status of elements such as B and Ca (Kawai et al, 1995 [25] ; Söderhäll, 1995 [52] ; Kwak et al, 1996 [30] ; Cakmak and Römheld, 1997 [10] ; Tomasbarberan et al, 1997 [59] ; Kim and Heinrich, 1997 [29] ; Ruiz et al, 1998 [46] , 1999 [47] ). In our experiment, the N dosage significantly affected the activities of PPO and POD (p < 0.001; Table 1), N2 and especially N1 presenting the highest activities, while N3 gave the lowest, with a reduction of 42 and 58 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1-MCP treatment completely suppressed leaf abscission in all cuttings, including those harvested at 0800 HR that had the lowest leaf preharvest TNC concentration but developed black shoot apices. Cuttings harvested at the onset of the photoperiod with a lower preharvest carbohydrate status, which was further depleted during dark storage (Rapaka et al, 2005) for metabolic processes, may have been subject to hydrolysis of phenolic glycoside esters by glycosidase enzymes (McConchie et al, 1994;Stephens et al, 2005). The cleavage of phenolic glycoside esters results in the production of a free sugar and a reactive phenolic moiety (Dey and Dixon, 1985), which can undergo nonenzymatic oxidation resulting in leaf blackening.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic glycoside esters hydrolysed by glycosidase enzymes result in a free sugar and a reactive phenolic moiety (Dey and Dixon, 1985), which can undergo nonenzymatic oxidation resulting in leaf blackening. McConchie et al (1994) suggested that glycosalated compounds may be cleaved under periods of carbohydrate stress. It is therefore possible that high glucose levels in protea leaves may Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for this notion came from findings that inflorescence removal and girdling significantly reduced or delayed leaf blackening (Brink and de Swardt, 1986;Dai and Paull, 1995;Paull et al, 1980;Reid et al, 1989;Paull and Dai, 1990;Stephens, 2001a;Tranter, 1989). The onset of postharvest leaf blackening has also been correlated with reduced leaf carbohydrate content (Bieleski et al, 1992;Jones and Clayton-Greene, 1992;McConchie and Lang, 1993b;McConchie et al, 1991McConchie et al, , 1994Newman et al, 1990). Under lighted conditions carbon assimilates and reserves in P. neriifolia shoots were converted to transport carbohydrates during inflorescence development (McConchie et al, 1991).…”
mentioning
confidence: 99%